2012
DOI: 10.1007/s00122-012-1987-3
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the effects of molecular marker polymorphisms in LcyE and CrtRB1 on provitamin A concentrations for 26 tropical maize populations

Abstract: Vitamin A deficiency (VAD) compromises immune function and is the leading cause of preventable blindness in children in many developing countries. Biofortification, or breeding staple food crops that are rich in micronutrients, provides a sustainable way to fight VAD and other micronutrient malnutrition problems. Polymorphisms, with associated molecular markers, have recently been identified for two loci, LcyE (lycopene epsilon cyclase) and CrtRB1 (β-carotene hydroxylase 1) that govern critical steps in the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
195
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(224 citation statements)
references
References 24 publications
20
195
1
8
Order By: Relevance
“…It also causes low resistance to infectious diseases and accounts for about 70% of childhood deaths across the world (Black et al 2008). Inbreds thus identified with high β-carotene (~15 µg/g) would be useful in developing provitamin A enriched hybrids to alleviate vitamin A deficiency (VAD) worldwide (Zhang et al 2012;Babu et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also causes low resistance to infectious diseases and accounts for about 70% of childhood deaths across the world (Black et al 2008). Inbreds thus identified with high β-carotene (~15 µg/g) would be useful in developing provitamin A enriched hybrids to alleviate vitamin A deficiency (VAD) worldwide (Zhang et al 2012;Babu et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Carotenoid profiling using HPLC to assess the concentration of β-carotene is expensive and time consuming. Thus selection based on the markers for favourable alleles of genes causing β-carotene enhancement in the pathway will be an effective approach for developing provitamin Arich maize genotypes (Yan et al 2010;Babu et al 2013) to alleviate VAD worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…The most important provitamin A enhancing alleles identified to date are lycopene epsilon cyclase (lcyE) and beta-carotene hydroxylase 1 (crtRB1) [51,52]. Validation experiments showed that the latter alone often doubles, and sometimes triples, the total concentration of provitamin A carotenoid content in maize grain, mainly by increasing the content of beta-carotene [53]. To date, in Africa, more than 40 provitamin A maize synthetics, single-cross hybrids, and three-way hybrids have been released in the DRC, Ghana, Malawi, Mali, Nigeria, Rwanda, Tanzania, Zambia, and Zimbabwe.…”
Section: Provitamin a Orange Maizementioning
confidence: 99%
“…Subsequently, genetic association mapping studies using three diverse maize germplasm panels, selected to encompass a wide range of carotenoid contents and ratios, were used to identify favorable alleles of genes encoding two key enzymes in the carotenoid biosynthetic pathway, lycopene epsilon cyclase (lycE) and beta-carotene hydroxylase 1 (crtRB1), which substantially affect the accumulation of beta-carotene in grain [27,28,29,30]. By using DNA markers identified for these two enzymes, the screening of germplasm has become faster and cheaper than selection based on HPLC methodology.…”
Section: Breeding Progress To Datementioning
confidence: 99%